Optimization of Cellulose-Based Hydrogel Synthesis Using Response Surface Methodology - Chin, Suk Fun; Jong, Shu Jun; Yeo, Jit Juan (Biointerface Research in Applied Chemistry, 2022)
Synthesis parameters have a significant effect on the properties of cellulose hydrogel. This study aimed to investigate the effects of synthesis parameters, e.g., the cellulose and crosslinkers concentration, on the hydrogels' swelling ratio under both heating and freezing gelation conditions, respectively. Cellulose hydrogels were prepared from wastepaper by the chemical crosslinking method by using epichlorohydrin ECH as a crosslinker. The effects of the synthesis parameters were compared and optimized by response surface methodology (RSM). Synthesized cellulose-based hydrogels under optimized conditions demonstrated an excellent swelling ratio of around 2800%. The optimum swelling ratio of 2467.72% was achieved from the experiment under the heating gelation condition. Thus the synthesized cellulose hydrogels are promising water-saving materials or controlled-release fertilizer carriers for sustainable horticultural and agricultural applications.